Determinan Struktur Modal Dalam Perspektif Pecking Order Theory Dan Agency Theory - Nana Umdiana; Shifa Tivana (Department of Accounting-Faculty of Economic and Business (FEB), 2020)
The capital structure seen from the perspective of pecking order theory explains that companies are more likely to prefer internal funding than external companies. Pecking Order Theory explains why highly profitable companies generally have less debt. This study aims to discuss Liquidity, Asset Structure, Business Risk, Growth Opportunity, Managerial Ownership of Capital Structures on Manufacturing Companies of the basic Consumer Good Industry Sector listed on the Indonesia Stock Exchange period 2016- 2019.This type of research is an associative causal research with the type of time series. The sample was selected using the purposive sampling method. Data analyzed amounted to 40. Data was tested using multiple linear regression analysis.The result of this study indicate that Liquidity is significant affect the Capital Structure. Asset Structure, Business Risk, Growth Opportunity, Managerial Ownership did not affect the Capital Structures.